Thermodynamic analysis and experimental study of partial oxidation reforming of biodiesel and hydrotreated vegetable oil for hydrogen-rich syngas production. (15th January 2019) - Lin, Ke-Wei; Wu, Horng-Wen
Graphical abstract: Highlights: A novel reformer of FAME and HVO on board is designed and studied by experiments. Carbon yield drops with raising O2 /FAME or O2 /HVO ratios by thermodynamic analysis. Reforming efficiency of a novel reformer for FAME is up to 72.80% by experiments. Reforming efficiency of a novel reformer for HVO is up to 62.87% by experiments. FAME has higher reforming efficiency and syngas yield than HVO by experiments. Abstract: Biofuel has benefits of reduction in CO2 and engine exhaust emissions, so it has been attracting more attention in the past few decades. In this study, the partial oxidation reforming of biodiesel (fatty acid methyl esters, hereafter, FAME) and a new generation renewable hydrotreated vegetable oil (HVO) are evaluated using a thermodynamic analysis and an experimental investigation. The thermodynamic analysis is used to evaluate the effect of the O2 /FAME and O2 /HVO molar ratios on hydrogen-rich syngas production. The results show that under the best operating conditions at 800 °C and an O2 /FAME molar ratio of 10, the concentration of the H2 is 21.96%, and the syngas yield is 45.50%; at an O2 /HVO molar ratio of 10, the concentration of H2 is 23.01%, and the syngas yield is 45.14%. In the FAME experimental results, when the air to fuel ratio is 4.70, the H2 concentration is 18.80%, the CO concentration is 22.87%, and the reforming efficiency is 72.80%. Moreover, for HVO reforming under the air to fuel ratio of 6.30, the H2 concentration is 17.65%; the CO concentration is 17.67%, and the reforming efficiency is 62.87%. Because the composition of HVO is more complex than that of FAME, the reforming efficiency for HVO is lower than that for FAME.